The Effect of Seed Priming Using Giberellic Acid (GA3) on Growth of Groundnut (Arachis hypogaea L.) and Lurik Groundnut (Arachis hypogaea L. var. Lurik) - Tamonob, Arshinto; Solichatun, Solichatun; Suratman, Suratman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Seed priming is a technique for treating seeds before germination to improve the quality of the plants produced. Seed priming can be done by soaking the seeds in various solutions, including hormone solutions. Groundnut (Arachis hypogaea L.) is the second most important commodity in Indonesia for both common and striated groundnut. This research aims to determine the effect of seed priming using the hormone gibberellic acid on the vegetative growth of peanuts and striated peanuts. This research used a completely randomized design with a factorial pattern; the first factor is variation in the type of peanut; The second factor is the variation in gibberellic acid concentration for seed priming, namely 0 ppm (only distilled water), 100 ppm, 200 ppm, 300 ppm and 400 ppm and without priming. Each treatment was carried out in 3 repetitions. The variables observed were plant wet weight, plant dry weight, chlorophyll content, number of leaves, shoot:root ratio. Quantitative data were analyzed using Analysis of Variance (ANOVA) and DMRT with a confidence level of 95%. The results of the research showed that seed priming treatment using the gibberellic acid hormone had a significant effect on the wet weight and dry weight of the plants; shoot:root ratio, and chlorophyll content of peanut and striated peanut leaves. Seed priming treatment using the hormone gibberellic acid had no significant effect on the number of leaves of ordinary peanuts and striated peanuts.